2022
DOI: 10.3390/economies10040090
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of the Financial–Growth Nexus in African Emerging Economies: The Case of a Macroprudential Policy Regime

Abstract: A panel data analysis of nonlinear financial growth dynamics in a macroprudential policy regime was conducted in a panel of 10 African emerging countries from 1983–2020, where it had been a non-prudential regime from 1983–1999 and a prudential regime from 2000–2020. The paper explored the validity of invented U-shape hypothesis in the prudential policy regime as well as the threshold level at which excessive finance boosts growth using the panel smooth transition regression (PSTR) model. The PSTR model was ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
3
1
Order By: Relevance
“…We conclude that non-linear causality extends from (FD) to (EG) in Algeria, which is consistent with findings of Al Khatib (2023), Golder et al (2023), Azimi (2022), Zungu (2022), Mei et al (2022), and Ductor and Grechyna (2013). These Studies found a Nonlinear causality from (FD) to (EG).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We conclude that non-linear causality extends from (FD) to (EG) in Algeria, which is consistent with findings of Al Khatib (2023), Golder et al (2023), Azimi (2022), Zungu (2022), Mei et al (2022), and Ductor and Grechyna (2013). These Studies found a Nonlinear causality from (FD) to (EG).…”
Section: Resultssupporting
confidence: 91%
“…Our results corroborate studies finding positive FD-EG links in developing countries (Abu-Bader & Abu-Qarn, 2008; Al khatib et al, 2022). However, the symmetric response conflicts with recent evidence of asymmetry in Africa (Chen et al, 2020; Zungu, 2022). Though nonlinear like Azimi (2022), our findings diverge from Ibrahim and Alagidede (2020) who uncovered asymmetric impacts in Ghana.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…analyzed asymmetric China finance indicator effects using NARDL, showing capital and money markets differently affect short and long-run EG Ref. [ 7 ]. revealed nonlinear FD-EG relationships in African economies [ 8 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Positive shocks from FD enhance EG while negative shocks hinder it [ 5 ]. Different finance indicators like capital markets, money markets, internet finance, and rural finance have varying short and long-run effects on EG depending on context and period [ [6] , [7] , [8] ]. However, excessive or inefficient FD can negatively impact EG beyond a threshold by misallocating capital or diverting resources to unproductive uses [ [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%